Durability aspects related to rubble stone masonry walls strengthened with reinforced micro-concrete layers - Pinho, Fernando F. S. (2014)
International Seminar on Seismic Risk and Rehabilitation of Stone Masonry Housing, Azores, Portugal, 1998